A Coupled, Zonally Averaged Atmosphere-Ocean Model: Variability of the Thermohaline Circulation - Stocker, Thomas F.; Wright, Daniel G.; Mysak, Lawrence A. (1992)
Two experiments with a recently developed zonally averaged climate model which includes the ocean's thermohaline circulation are performed. The first experiment simulates a global thermohaline circulation in which deep water is formed in the North Atlantic, flows as a deep current into the Pacific basin and then upwells. The water is returned as a near-surface flow through the Indian Ocean into the South Atlantic Gordon, 1986. The present model reproduces a global deep circulation under present-day forcing and shows that the zonal atmospheric water vapor transport is of importance. The second experiment studies the effect of glacial meltwater runoff at different latitudes on the thermohaline circulation, meridional heat flux and surface air temperature. Depending on the strength and position of the forcing anomaly, severe cooling can be observed in high northern latitudes. The mechanism may provide further insight into the Younger Dryas climate event. This article is from 'Proceedings of the International Conference on the Role of the Polar Regions in Global Change Held in Fairbanks, Alaska on 11-15 June 1990. Volume 1', AD-A253 027, p291-295. See also Volume 2, AD-A253 028.